Determinants of Taxpayers’ Compliance among MSMEs in Thamrin City, Jakarta, Indonesia - herianti, Eva (International Journal of Economics, Business, and Entrepreneurship, 2023)
This study aims to determine the effect of public trust, self-assessment system, and value of religiosity of taxpayer compliance, either partially or simultaneously. This study was conducted in Thamrin City in Central Jakarta. The number of the respondents comprised 95 respondents, and this number was obtained from MSMEs that have a TIN through the distribution of questionnaires using non-probability sampling. SEM Partial Least Square (SmartPLS 3.0) was used as a data analysis tool. The results of this study indicate that: (1) public trust has a positive and significant effect on the taxpayer compliance; (2) self-assessment system has a positive and significant effect on the taxpayers’ compliance; (3) value of religiosity has a positive and significant effect on the taxpayer compliance. This study was conducted only for MSMEs that have a TIN at a mining site located in Thamrin City, Central Jakarta. This study was undertaken amid the COVID-19 pandemic, causing researchers to encounter difficulties and various obstacles in terms of licensing. Researchers only tested three independent variables on taxpayer compliance. For the Directorate General of Taxes, the results of this study are expected to improve the MSME taxpayer compliance so that they can be used as material for consideration and evaluation in formulating policies regarding taxpayer compliance.